Mesenchymal Stem Cells Transplantation following Partial Hepatectomy: A New Concept to Promote Liver Regeneration—Systematic Review of the Literature Focused on Experimental Studies in Rodent Models - Ioannis G. Papanikolaou; Charalambos Katselis; Konstantinos Apostolou; Themistoklis Feretis; Maria Lymperi; Manousos M. Konstadoulakis; Apostolos E. Papalois; George C. Zografos (Stem Cells International)
Mesenchymal stem cells (MSCs) are an attractive source for regenerative medicine because they are easily accessible through minimally invasive methods and have the potential to enhance liver regeneration (LG) and improve liver function, following partial hepatectomy (PH) and acute or chronic liver injury. A systematic review of the literature was conducted for articles published up to September 1st, 2016, using the MEDLINE database. The keywords that were used in various combinations were as follows: “Mesenchymal stem cells”, “transplantation”, “stem cells”, “adipose tissue derived stem cells”, “bone marrow-derived stem cells”, “partial hepatectomy”, “acute liver failure”, “chronic liver failure”, “liver fibrosis”, “liver cirrhosis”, “rats”, “mice”, and “liver regeneration”. All introduced keywords were searched for separately in MeSH Database to control relevance and terminological accuracy and validity. A total of 41 articles were identified for potential inclusion and reviewed in detail. After a strict selection process, a total of 28 articles were excluded, leaving 13 articles to form the basis of this systematic review. MSCs transplantation promoted LG and improved liver function. Furthermore, MSCs had the ability to differentiate in hepatocyte-like cells, increase survival, and protect hepatocytes by paracrine mechanisms. MSCs transplantation may provide beneficial effects in the process of LG after PH and acute or chronic liver injury. They may represent a new therapeutic option to treat posthepatectomy acute liver failure.